Anti-Hypertensive and Anti-Hypercholesterolemic Effects of Protein Hydrolysates from (Phaseolus vulgaris) L. in Functional Beverage - Bolayo, Yvonne; Torio, Mary Ann (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
The study aimed to formulate a functional beverage from common bean seeds, isolate the proteins and evaluate their anti-hypertensive and anti-cholesterolemic properties. White common beans (Phaseolus vulgaris L.) mature seeds were used to prepare the beverage. Proteins isolated from the beverage were subjected to digestion with pepsin and combined enzymes including trypsin, thermolysin, and chymotrypsin. The unhydrolyzed beverage and protein hydrolysates were subsequently tested for Angiotensin Converting Enzyme (ACE) inhibition and cholesterol micellar solubility inhibition. The results showed that both unhydrolyzed and hydrolyzed proteins exhibited blood pressure and cholesterol-lowering properties, with high ACE inhibition (77.60%) and cholesterol micellar solubility inhibition (27.38%). The formulated functional beverage from white common bean seeds has potential for preventing hypertension and hypercholesterolemia. This study offers a theoretical foundation for the formulation of functional beverages or bean-based food products by food companies.